Protective Effects of Dioscin Against Doxorubicin-Induced Hepatotoxicity Via Regulation of Sirt1/FOXO1/NF-κb Signal - Shasha Song; Liang Chu; Huifang Liang; Jin Chen; Junnan Liang; Zhao Huang; Bixiang Zhang; Xiaoping Chen (Frontiers Media S.A., 2019)
Doxorubicin (Dox), an antitumor antibiotic, has therapeutic effects on many kinds of tumors. However, Dox can produce some serious side effects that limit its clinical application. Thus, exploration of effective drug targets or active lead compounds against Dox-induced organ damage is necessary. Dioscin, one natural product, has potent effects against Dox-induced renal injury and cardiotoxicity. However, the effects of dioscin on Dox-induced hepatotoxicity have not been reported. In this study, the results showed that dioscin significantly ameliorated Dox-induced cell injury, reduced reactive oxygen species (ROS) level, and suppressed cell apoptosis in alpha mouse liver 12 (AML-12) cells caused by Dox. In vivo, dioscin evidently decreased the levels of alanine transaminase (ALT), aspartate transaminase (AST), malondialdehyde (MDA); increased the levels of superoxide dismutase (SOD), glutathione (GSH), and glutathione peroxidase (GSH-Px); and alleviated liver injury. Mechanism study showed that dioscin remarkably up-regulated the expression levels of silent information regulator 1 (Sirt1) and heme oxygenase-1 (HO-1) via increase of the nuclear translocation of NF-E2-related factor 2 (Nrf2) and suppressed the expression levels of forkhead box protein O1 (FOXO1) and kelch-like ECH-associated protein-1 (Keap1) to inhibit oxidative stress. Furthermore, dioscin obviously decreased the nuclear translocation of nuclear factor κB (NF-κB) and the mRNA levels of tumor necrosis factor alpha (TNF-α), interleukin 1β (IL-1β), and interleukin 6 (IL-6) to suppress inflammation. Meanwhile, dioscin significantly regulated tumor suppressor P53 (P53) expression level and BCL-2-associated X (BAX)/BCL-2 apoptosis regulator (BCL-2) ratio to inhibit cell apoptosis. These results were further validated by knockdown of Sirt1 using siRNA silencing in AML-12 cells, which confirmed that the target of dioscin against Dox-induced hepatotoxicity was Sirt1/FOXO1/NF-κB signal. In short, our findings showed that dioscin exhibited protective effects against Dox-induced liver damage via suppression of oxidative stress, inflammation, and apoptosis, which should be developed as one new candidate for the prevention of Dox-induced liver injury in the future.